2021
DOI: 10.3390/ma14133570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Geometric and Crystallographic Factors on the Reliability of Al/Si Vertically Cracked Nanofilm/Substrate Systems

Abstract: In this study, tensile tests on aluminum/silicon vertically cracked nanofilm/substrate systems were performed using atomistic simulations. Various crystallographic orientations and thicknesses of the aluminum nanofilms were considered to analyze the effects of these factors on the reliability of the nanofilm/substrate systems. The results show that systems with some specific crystallographic orientations have lower reliability compared to the other orientations because of the penetration of the vertical crack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Fracture energy ( G ) for the SiNW failure was determined from the area under the tensile stress and strain curves and was calculated using the following formula [ 43 ]: where represents the critical strain for the SiNW failure, and the SI unit of G is GJ/m 3 . According to Equation (15), the G value for the pure [111]-oriented SiNW was 1.67 GJ/m 3 , whereas that for the SiNW failure in the case of Model-1 was 4.16 GJ/m 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fracture energy ( G ) for the SiNW failure was determined from the area under the tensile stress and strain curves and was calculated using the following formula [ 43 ]: where represents the critical strain for the SiNW failure, and the SI unit of G is GJ/m 3 . According to Equation (15), the G value for the pure [111]-oriented SiNW was 1.67 GJ/m 3 , whereas that for the SiNW failure in the case of Model-1 was 4.16 GJ/m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Fracture energy (G) for the SiNW failure was determined from the area under the tensile stress and strain curves and was calculated using the following formula [43]:…”
Section: Failure Mechanism Of the Si/cnt Nanocompositementioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have attempted to analyze the nonlinear behavior of nanomaterials using atomistic simulations. Recently, it was confirmed that crack penetration, contrary to the existing theory, occurred in an aluminum/silicon vertically cracked nanofilm/substrate system with a coherent interface when the system was under tension [ 8 ]. Silicon generally exhibits brittle properties, but it has been confirmed that silicon nanowires of a certain size or less cause ductile transition [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, research on Cu/CNT composite materials has mainly focused on the performance and efficiency of devices through experimental methods, while research on mechanical reliability from a fracture mechanics perspective is insufficient. Therefore, in this study, a fracture mechanics analysis was conducted on a Cu/CNT composite specimen with a half-crack through molecular statics (MS) simulation [ 8 ]. The effect of CNT size in the composite material on the mechanical reliability of the entire composite material was analyzed, and the fracture toughness of the Cu/CNT composite material was evaluated.…”
Section: Introductionmentioning
confidence: 99%